Civil Constabulary Reserve, 'Daily Chronicle', 14 May 1926
1926-05-14 "Civil Constabulary Reserve, 'Daily Chronicle', 14 May 1926" [g0596001.jpg], 14 May 1926, London Daily Chronicle At the beginning of the strike, the Home Secretary had broadcast an appeal for 30,000 more special constables to be enrolled at once to swell the total to 200,000, some 40,000 in London alone. On 7 May, the Cabinet decided to set up in addition a paid Civil Constabulary Force (CCF) and Territorial Army units were invited to volunteer for this force, although the TA was not itself called out. Recruitment for the CCF was just beginning when the strike came to an end. Government Objectives